Wear and Dynamic Mechanical Analysis (DMA) of Samples Produced via Fused Deposition Modelling (FDM) 3D Printing Method - Struz, Jiri; Trochta, Miroslav; Hruzik, Lukas; Pistacek, Daniel; Stawarz, Sylwester; Kucharczyk, Wojciech; Rucki, Miroslaw (Polymers, 2024)
In recent years, plastic and metal 3D printing has experienced massive development in the professional and hobby spheres, especially for rapid prototyping, reverse engineering, maintenance and quick repairs. However, this technology is limited by a number of factors, with the most common being the cost and availability of the technology but also the lack of information on material properties. This study focuses on investigating the material properties of PLA, PETG, HIPS, PA, ABS and ASA in order to elucidate their behavior in terms of wear and thermal resistance. The research builds on previous studies focusing on the mechanical properties of these materials and includes wear testing and DMA analysis. Weight loss, frictional forces, and frictional work including relative frictional work are recorded as part of this testing. The storage modulus and loss modulus including tan(δ) were then measured using DMA.
Keywords: loss modulus; weight loss; DMA; storage modulus; glass transition temperature; FDM; coefficient of friction